1995
DOI: 10.1080/01635589509514386
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids induce morphological changes in human mammary epithelial cell cultures

Abstract: Epidemiological studies suggest that carotenoids may play a role in human breast carcinogenesis. To identify an anticarcinogenic mechanism, a laboratory model for examination of biologic effects is required. Efficacy of tetrahydrofuran (THF) for delivery of beta-carotene to a human mammary epithelial cell line has not been reported, and biologic effects of carotenoids on normal mammary epithelial cells or mammary epithelial cell lines have not been described. In these studies, we examined MCF-10A cells treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(16 citation statements)
references
References 26 publications
2
13
0
1
Order By: Relevance
“…An accumulation of 0.004 nmol/lO%ells was found when 7 pM $-carotene was added to MCFlOA human mammary epithelial cells for five days (43). These cellular concentrations are within the range reported in similar studies using different cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…An accumulation of 0.004 nmol/lO%ells was found when 7 pM $-carotene was added to MCFlOA human mammary epithelial cells for five days (43). These cellular concentrations are within the range reported in similar studies using different cell lines.…”
Section: Discussionsupporting
confidence: 84%
“…While there is good evidence from cell-culture and animal studies supporting the role of dietary components in mammary cell tumorigenesis [14][15][16] results from studies in women have been variable. Red meat intake has been hypothesized to increase breast cancer risk, but while case-control and ecologic studies have supported a positive association, prospective cohort studies have been inconsistent.…”
Section: Introductionmentioning
confidence: 91%
“…Zhi et al (2000) showed that newborn rat calvarial osteoblastic cells cultured in all-trans retinoic acid for 24 h up-regulate the proliferation of osteoblasts. Rock et al (1995) noted that carotenoids promote human mammary epithelial cell proliferation and differentiation. In the current study, cell proliferation was significantly improved when BMEC were treated with VA, which is consistent with previous results.…”
Section: Discussionmentioning
confidence: 99%